2004
DOI: 10.1007/s11661-004-0312-4
|View full text |Cite
|
Sign up to set email alerts
|

Solid particle erosion of Al alloy and Al-alloy composites: Effect of heat treatment and angle of impingement

Abstract: Erosive wear behavior of the as-cast and heat-treated Al alloy and the Al-alloy-SiC particle composite against Al 2 O 3 erodent has been examined at different angles of impingement (15 to 90 deg). It has been noted that the cast Al alloy exhibited a higher erosion rate than the heat-treated alloy and composites irrespective of the angle of impingement. It is noted that the as-cast and heat-treated Al alloy exhibited a maximum wear rate at the 45 deg angle of impingement, whereas the composite, in as-cast as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Das et al. 114 performed solid particle erosion experiments of SiC particle reinforced Al alloy composites (SiC/Al). The average size of SiC particle was 75 µm, and its weight content was 10 wt%.…”
Section: Metal Matrix Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…Das et al. 114 performed solid particle erosion experiments of SiC particle reinforced Al alloy composites (SiC/Al). The average size of SiC particle was 75 µm, and its weight content was 10 wt%.…”
Section: Metal Matrix Compositesmentioning
confidence: 99%
“…Their results showed that the inclusion of in situ TiB 2 particles improved the erosion resistance of unreinforced A356 alloy as in the case of Das et al.’s study. 114 They supposed that the higher hardness of TiB 2 than that of SiC erodent particle and good bonding strength between TiB 2 particles and Al 116 led to the improvement of erosion resistance compared with the neat A356 alloy. Similar result was obtained in solid particle erosion experiments of aluminum reinforced with redmud composite 117 and bronze reinforced with diamond particulate composite.…”
Section: Metal Matrix Compositesmentioning
confidence: 99%
“…Finnie (1995 classified them in 3 categories: fluid flow conditions, particle properties and surface properties. Some of these have been studied by others authors: impact angle (Das et al, 2004;Nguyen et al, 2014), particle speed (Stevenson et al, 1995;Yabuki et al, 1999) and particle rotation (Deng et al, 2004;Nguyen et al 2015). And among the particle properties (Bousser et al, 2013;Murugesh et al, 1991): size (Macchini et al, 2013;Nguyen et al, 2016;Venugopal Reddy et al, 1991), shape (Akbarzadeh et al, 2012;Feng et al, 1999;Laguna-Camacho et al, 2015;Naveed et al, 2016;Vite-Torres et al, 2013), and hardness (Arabnejad et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The flow of coal powder air mixture wrapping the inner shrouds and it create eddies which accelerate erosion. Erosion and wear are the mechanism of mass loss due to abrasion at high velocity of coal powder and subjected to continuous impingement of coal particles at leading edges of the discharge points [1], [2]. Erosion in the product are many reasons, inadequate primary air, higher swirl of fuel-air mixer, fuel flow velocity, fire ball location, tip shape, overheating and temperature of the system [4].…”
Section: Introductionmentioning
confidence: 99%